Influência de Produtos de Higiene Pessoal e Limpeza na Concentração de Sólidos Totais, DBO, DQO, Nitrogênio Total e Fósforo Total do Esgoto Doméstico - Martins, Augusto Severo (2018)
Due to the high consumption of personal care and cleaning products, quantifying the influence of these products on the quality of domestic sewage can contribute to the preservation of water bodies. Part of the domestic sewage is released into the environment without any form of treatment. As they pass through the treatment plant, a high concentration of pollutants raises the cost and difficulty of treating this efleunte. The objective of this study is to evaluate the contribution of the amount used of dental cream, shampoos, liquid detergents, powder detergents and concentrated softeners for the sewage organic load through an experimental analysis of solutions produced with such products. Distilled water solutions were produced, based on the daily quantity of products used and daily per capita volume of sewage from the city of Uberlândia - MG. The amount of product used in the production of the solutions was varied according to the recommended daily consumption. The parameters TS, BOD, COD, Total Nitrogen and Total Phosphorus were analyzed. The tests allowed to evaluate if only the products contribute to the considered parameters and if the quantity of product used interferes directly. For this verification, mean values of domestic sewage and wastewater from the points of use of the products were searched in national and international literature, and comparisons were made. The quantity of product is directly proportional to the alteration of the analyzed parameters. The sum of the contributions of the five products analyzed represented 12.34% of TS, 20.05% of COD, 0.17% of Ntotal and 0.49% of Ptotal in relation to the average concentrations reported in the literature for domestic sewage.